The Influence of Drift Angle on the Flow Field around KVLCC2 Tanker Using CFD - عباس, نوار; العجي, نرمين (Latakia University Journal -Engineering Sciences Series, 2022)
In this research, the flow around the Tanker KVLCC2 model is calculated and analyzed by using a Computational Fluid Dynamics (CFD). It was focused on the flow behind the hull at the propeller plane, due to its importance in determining of the propeller working conditions. Reynolds Averaged Navier Stoke method (RANS) and model were used to solve Navier Stokes equations, where the equations were approximated using Finite Volumes Method (FVM). The program ANSYS was used in this research. The flow around the tanker under different sailing conditions (at straight course and at different drift angles) were performed, the resistance and moments affecting the tanker during sailing was calculated as well the pressure distribution on the hull surface. The numerical results were compared with experimental data. This Comparison showed how much CFD technology is accurate in calculation of this type of flow cases.